The conversion of monoculture sugarcane to a tree-based agroforestry system increases total carbon sequestration and soil macrofauna population - Cahyo Prayogo; Novi Arfarita (Journal of Degraded and Mining Lands Management, 2022)
Vegetations accumulate carbon (C) from the atmosphere in the form of tree biomass, producing litter which then becomes the main input of soil organic matter. The accumulation of soil organic matter provides food and energy for soil macrofauna to help maintain soil fertility. Total C accumulation is affected by land use changes which can then reduce soil ecosystem and ecological functioning. This study examined the impact of land use conversion from monoculture sugarcane to a tree-based agroforestry system. The results showed that the land use changes affected soil texture, bulk density, soil organic matter, and total C sequestration. The total C sequestration under 5 years old sengon (Paraserianthes moluccana) agroforestry system was almost double that of total C sequestration 2 times or even 5 times ratooned monoculture sugarcane (Saccharum officinarum). The lowest IVI of soil macrofauna was detected under 1-year-old sengon agroforestry system before it was getting lowered under a longer period of cultivation, whilst the highest population was detected under 5 years old Sengon. Multivariate analysis, which was employed to detect the impact of land use changes, could cluster and group the effect of treatments based on selected variables such as soil physical, chemicals, and soil macrofauna structure and diversity, which accounted for 97.75% of the total variance. There was a strong relationship between the abundance of Formicidae sp. and Carabidae sp.